Modernity's classics - Wagner, Rudolf G.; Humphreys, Sarah C. (Transcultural Research - Heidelberg Studies on Asia and Europe in a Global Context, 2013)
This book presents critical studies of modern reconfigurations of conceptions of the past, of the 'classical', and of national heritage. Its scope is global (China, India, Egypt, Iran, Judaism, the Greco-Roman world) and inter-disciplinary (textual philology, history of art and architecture, philosophy, gardening). Its emphasis is on the complexity of the modernization process and of reactions to it: ideas and technologies travelled from India to Iran and from Japan to China, while reactions show tensions between museumization and the recreation of 'presence'. It challenges readers to rethink the assumptions of the disciplines in which they were trained